Psychological performance and organizational performance of Sport firms: An impact of public managerial quality in the Chinese sports industry - Zhuoyuan, Yu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The basic purpose of this research study is to measure the psychological performance and organizational performance of sports firms an essential impact of public managerial quality in the Chinese industry. This research study used the national interest concept and also that mercantilism theory to measure the development of the drive of china's sports industry. This research study based on primary data analysis for this purpose used different questions related to the sport performance in china. Data collected from the sports firms regarding psychological performance and organizational performance. These data analysis through smart PLS software by using different techniques such as one-way ANOVA test analysis, factor analysis, tree analysis, PLS Algorithm model, and regression analysis in between dependent and independent variables. Psychological performance considers an independent variable, and public managerial quality presents that role as a mediator. The organizational performance of the sports industry is dependent. There are sub-variables related to organizational performance, including goal approaches, resources, management approach, organizational strategy, etc. Results found that psychological performance plays an inverse relation with the organizational performance of the sports industry. The organizational strategy, public managerial quality shows a positive and significant impact on the Chinese sports industry and its organizational performance.